Effects of the pesticide chlorpyrifos on breast cancer disease. Implication of epigenetic mechanisms. Issue 186 (February 2019) - Ventura, C.; Zappia, C.D.; Lasagna, M.; Pavicic, W.; Richard, S.; Bolzan, A.D.; Monczor, F.; Núñez, M.; Cocca, C.
Graphical abstract: Highlights: CPF is an organophosphate pesticide fully used for agricultural pest control. CPF increases tumor incidence and reduces latency period in NMU-induced mammary tumors. CPF decreases steroid hormone receptor expression in NMU-induced mammary tumors. CPF alters HDAC1 mRNA expression in mammary gland of chronically exposed rats. Abstract: Chlorpyrifos (CPF) is an organophosphorus pesticide used for agricultural pest control all over the world. We have previously demonstrated that environmental concentrations of this pesticide alter mammary gland histological structure and hormonal balance in rats chronically exposed. In this work, we analyzed the effects of CPF on mammary tumors development. Our results demonstrated that CPF increases tumor incidence and reduces latency of NMU-induced mammary tumors. Although no changes were observed in tumor growth rate, we found a reduced steroid hormone receptor expression in the tumors of animals exposed to the pesticide. Moreover, we analyzed the role of epigenetic mechanisms in CPF effects. Our results indicated that CPF alters HDAC1 mRNA expression in mammary gland, although no changes were observed in DNA methylation. In summary, we demonstrate that the exposure to CPF promotes mammary tumors development with a reduced steroid receptors expression. It has also been found that CPF affects HDAC1 mRNA levels in mammary tissue pointing that CPF may act as a breast cancer risk factor.